A influência do tamanho de grão ferrítico da peça na integridade superficial de peças erodidas - Cruz Junior, Eli Jorge da [UNESP] (2015)
Electrical Discharge Machining (EDM) is a non-conventional machining process which is based on material removal by successive electrical discharges. During each discharge temperatures can reach 12,000 °C, followed by rapid cooling, creating a heat-affected zone on the workpiece surface. This zone has different properties with respect to the base material (bulk) such as higher hardness, microstructural composition and may still exist microcracks that will affect the performance of the machined part. This research determined the influence of workpiece grain size on the machined surface integrity. Low carbon steel named commercially as COS AR 60 with different ferritic grain sizes was applied to machining tests. Surface integrity of the machined subsurface (white layer, heat- affected zone and bulk) was evaluated by considering microhardness gradient, microstructure composition and microcracks formation. The results show that the roughing condition increases the white layer but it is smaller for ultrafine-grained material. The hardness is highest in white layer when compared to other layers. The materials with ultrafine grains present a softer microhardness transition as compared with the conventional grains, which may improve the performance of the part in service from the standpoint of crack propagation